MODEL EVALUASI PEMBELAJARAN SENI TARI DI SMA NEGERI 2 PADANG - Vega Minda Marizana; Yuliasma Yuliasma; Zora Iriani (SENDRATASIK UNP, 2013)
Abstract This study aims to determine the evaluation model used by teachers in teaching dance at SMA Negeri 2 Padang. This research described the effectiveness of evaluation model that is implemented in learning dance. This qualitative research used descriptive analysis, which seeks to create a description on the actual situation in accordance with the reality. Data were taken from 3 meetings of learning process. The sample in this study was the dance teacher SMAN 2 Padang and 30 students of XI IPA 1. Techniques of data collection were observation and interviews. The findings of the study shows that the evaluation model used by teachers in teaching dance is a congruence with evaluation model (appropriate), because in Teaching and Learning processes are in accordance with the purpose of learning dance, learning experience, and learning outcomes of the students. The instruments to measure students’ achievement were practice tests and theory mastery test. Meanwhile, students’ learning outcomes are seen from three aspects: cognitive, affective and psychomotor. Based on the data that has been collected, the effectiveness of evaluation model can be seen from the correspondence between the learning objectives to understand all the material in the lesson plans with students’ learning outcomes is very significant.